The purple swamp hen and other stories - Lively, Penelope, 1933- (Viking, 2017)
"A glimmering collection of new short fiction from the Booker Prize winner and national bestselling author of How It All Began. In such acclaimed novels as The Photograph, Family Album, and How It All Began, Penelope Lively has captivated readers with her singular blend of wisdom, elegance, and humor. Now, in her first story collection in decades, Lively takes up themes of history, family, and relationships across varied and vividly rendered settings. In the title story, a Mediterranean purple swamp hen chronicles the secrets and scandals of Quintus Pompeius's villa, culminating with his narrow escape from the lava and ash of Vesuvius. "Abroad" captures the low point of an artist couple's tumultuous European road trip, trapped in a remote Spanish farmhouse and forced to paint a family mural and pitch in with chores to pay for repairs to their broken-down car. Other stories reveal friends and lovers in fateful moments of indiscretion, discovery, and even retribution--as in "The Third Wife," when a woman learns her husband to be a serial con artist and turns a house hunting trip into an elaborately staged revenge trap"--